2016
DOI: 10.1002/jsfa.8125
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks and factors influencing microbiological contamination of fresh produce

Abstract: Fresh fruits and vegetables are nutritionally well-recognised as healthy components in diets. The microbiological foodborne outbreaks associated with the consumption of fresh produce have been increasing. Salmonella spp., Escherichia coli O157:H7, Staphylococcus aureus, Campylobacter spp. and Listeria monocytogenes are the most common pathogens that contaminate fresh produce. This review discusses recent foodborne outbreaks linked to fresh produce, factors that affect microbiological contamination and measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(85 citation statements)
references
References 67 publications
(54 reference statements)
1
72
0
Order By: Relevance
“…However, and as stated in the literature (Franz & van Bruggen, ), the data compiled in the present study revealed the contamination of RTE foodstuffs by other, less common serovars of Salmonella . A total of 53 different serovars were reported as responsible for RTE food–related disease outbreaks, with Salmonella Saintpaul (Gieraltowski et al., ; O'Mahony et al., ), Salmonella Javiana (Blostein, ; Lehmacher, Bockemuhl, & Aleksic, ), Salmonella Poona (Bowen, Fry, Richards, & Beauchat, ; Wadamori et al., ), Salmonella Typhimurium (Harris et al., ; Horby et al., ; Sotir et al., ), Salmonella Newport (Angelo et al., ; van Beneden et al., ), Salmonella Muenchen (CDC ; Proctor et al., ), and Salmonella Rubislaw (Lehmacher et al., ) accounting for the majority of the cases (54.2% of total considered Salmonella cases) in this study. Salmonella is widespread in the environment and normally found in farm effluents and any material subjected to fecal contamination (Arrus, Holley, Ominski, Tenuta, & Blank, ; Martinez‐Urtaza et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…However, and as stated in the literature (Franz & van Bruggen, ), the data compiled in the present study revealed the contamination of RTE foodstuffs by other, less common serovars of Salmonella . A total of 53 different serovars were reported as responsible for RTE food–related disease outbreaks, with Salmonella Saintpaul (Gieraltowski et al., ; O'Mahony et al., ), Salmonella Javiana (Blostein, ; Lehmacher, Bockemuhl, & Aleksic, ), Salmonella Poona (Bowen, Fry, Richards, & Beauchat, ; Wadamori et al., ), Salmonella Typhimurium (Harris et al., ; Horby et al., ; Sotir et al., ), Salmonella Newport (Angelo et al., ; van Beneden et al., ), Salmonella Muenchen (CDC ; Proctor et al., ), and Salmonella Rubislaw (Lehmacher et al., ) accounting for the majority of the cases (54.2% of total considered Salmonella cases) in this study. Salmonella is widespread in the environment and normally found in farm effluents and any material subjected to fecal contamination (Arrus, Holley, Ominski, Tenuta, & Blank, ; Martinez‐Urtaza et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The hurdle approach has been proposed to some extent before. Some studies have suggested the use of natural agents as hurdles, other the use of bacteriocins, modified athmosphere and a strict management of temperature and storage times (Wadamori et al, 2017). But, regardless of the type of hurdles, the basis of the hurdle concept is a combined approach incorporating two or more practices (or hurdles), each of which may not be sufficient to control foodborne pathogens by itself, but together they can reduce or eliminate microbial hazards (Leistner, 2000).…”
Section: The Hurdle Conceptmentioning
confidence: 99%
“…Consumers believe that organic food are healthier and safer than conventional foods as synthetic fertilizers are avoided, in addition to the perceived benefits to the environment, animal's welfare, and workers safety (Winter and Davis ; Thogersen et al . ; Reganold and Wachter ; Asioli et al . ).…”
Section: Introductionmentioning
confidence: 99%